Paediatric mild head injury: is routine admission to a tertiary trauma hospital necessary?. Issue 3 (18th September 2017) - Tallapragada, Krishna; Peddada, Ratna Soundarya; Dexter, Mark
Abstract : Background: Previous studies have shown that children with isolated linear skull fractures have excellent clinical outcomes and low risk of surgery. We wish to identify other injury patterns within the spectrum of paediatric mild head injury, which need only conservative management. Children with low risk of evolving neurosurgical lesions could be safely managed in primary hospitals. Methods: We retrospectively analysed all children with mild head injury (i.e. admission Glasgow coma score 13–15) and skull fracture or haematoma on a head computed tomography scan admitted to Westmead Children's Hospital, Sydney over the years 2009–2014. Data were collected regarding demographics, clinical findings, mechanism of injury, head computed tomography scan findings, neurosurgical intervention, outcome and length of admission. Wilcoxon paired test was used with P value <0.05 considered significant. Results: Four hundred and ten children were analysed. Three hundred and eighty‐one (93%) children were managed conservatively, 18 (4%) underwent evacuation of extradural haematoma (TBI surgery) and 11 (3%) needed fracture repair surgery. Two children evolved a surgical lesion 24 h post‐admission. Only 17 of 214 children transferred from peripheral hospitals needed neurosurgery. Overall outcomes: zero deaths, one needed brain injury rehabilitation and 63 needed child protection unit intervention. Seventy‐five percentage of children with non‐surgical lesions were discharged within 2 days. Eighty‐three percentage of road transfers were discharged within 3 days. Conclusions: Children with small intracranial haematomas and/or skull fractures who need no surgery only require brief inpatient symptomatic treatment and could be safely managed in primary hospitals. Improved tertiary hospital transfer guidelines with protocols to manage clinical deterioration could have cost benefit without risking patient safety.